Caring for women experiencing miscarriage and the importance of good communication. Issue 11 (November 2022) - Hart, Sarah; Walker, Kate F.
Abstract: The importance of good quality nursing care for pregnancy loss patients can not be underestimated. Pregnancy loss is comparable to any other kind of loss and patients have noted that the nursing care they receive while in hospital can either add to or alleviate their distress. Central to this is the communication used by nurses and healthcare professionals. Bad communication is costly to the NHS and can cause unnecessary emotional harm. Research shows that additional education and training for nurses, based on patient feedback and collaboration with pregnancy loss charities, would be a positive step in ensuring that the care given is patient centred and compassionate.